The Application of Local Potential-Based E-Modules to Improve Students Critical Thinking Skills in Biology Learning: A Systematic Literature Review - Yena Harmelayati; Riandi; Amprasto (Jurnal Penelitian Pendidikan IPA, 2026)
The application of e-modules based on local potential in biology learning is an innovation that can integrate science with the local environment. This study aims to analyze the influence, effectiveness, and challenges of applying e-modules to improve critical thinking skills. A systematic literature review was adopted as the research method after selecting and screening articles using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol. Articles published from 2017 to 2026 were retrieved from Scopus. Of the 109 articles identified, 11 articles were selected based on inclusion and exclusion criteria. The results show that electronic modules based on local potential are effective in improving students' critical thinking skills, scientific literacy, problem solving, and other 21st-century skills. The integration of local potential can help students connect scientific concepts with everyday life, creating more relevant and in-depth learning based on reality. However, challenges remain in terms of digital literacy, design, and curriculum suitability. This study is expected to serve as the basis for the development of contextual biology e-modules oriented towards higher-order thinking skills.